2013
DOI: 10.1007/s10584-013-0954-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling high-impact weather and climate: lessons from a tropical cyclone perspective

Abstract: Although the societal impact of a weather event increases with the rarity of the event, our current ability to assess extreme events and their impacts is limited by not only rarity but also by current model fidelity and a lack of understanding and capacity to model the underlying physical processes. This challenge is driving fresh approaches to assess highimpact weather and climate. Recent lessons learned in modeling high-impact weather and climate are presented using the case of tropical cyclones as an illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 49 publications
1
111
0
Order By: Relevance
“…We further compare the observed changes to recent climate simulations with the dynamical downscaling results of Bender et al (2010), Done et al (2012), and Wu and Zhao (2012).…”
Section: Datamentioning
confidence: 97%
See 4 more Smart Citations
“…We further compare the observed changes to recent climate simulations with the dynamical downscaling results of Bender et al (2010), Done et al (2012), and Wu and Zhao (2012).…”
Section: Datamentioning
confidence: 97%
“…Bender et al (2010) found that for each°C of global warming the proportion of Cat 4-5 hurricanes increased by *11 % and the proportion of Cat 1-2 hurricanes decreased by *7 %. Done et al (2012) applied Weibull and Generalized Pareto distributions to assess the expected changes in future North Atlantic hurricane extremes based on changes to the mean and variance of the truncated distribution predicted by the NCAR Nested Regional Climate Model (Done et al 2012). Both approaches showed that relatively modest increases in the mean (3 %) and standard deviation of (7 %) produced an increase in the proportion of Cat 4-5 hurricanes of *15 % per°C of global warming.…”
Section: Comparison With Model Simulationsmentioning
confidence: 99%
See 3 more Smart Citations